Letter from James Curtis Booth to Jesse Y. Burk - Booth, James Curtis (1884)
A letter of recommendation from James Curtis Booth (1810-1888) to Rev. Jesse Y. Burk, Secretary of the Board of Trustees of the University of Pennsylvania, recommending chemist Prof. Samuel P. Sadtler (1847-1923).
Keywords: Booth, James Curtis, 1810-1888; Sadtler, Samuel P. (Samuel Philip), 1847-1923; Chemistry teachers